Mesalazine-Induced Myopericarditis in a Patient with a Recent Diagnosis of Crohn’s Disease: Apropos of a Case - Michele Sorleto; Stefanie Dürrwald; Marcus Wiemer (Case Reports in Cardiology)
Mesalazine- (5-aminosalicylic acid-) containing products are a well-known treatment for inflammatory bowel disease, often as first line. Myocarditis is recognized as a very rare possible side effect of this drug treatment. We present a case of mesalazine-induced myopericarditis that was successfully improved by immediate cessation of the medication.